Otimização e escalonamento da produção do agente de controle biológico Beauveria bassiana em cultivo submerso - Basso, Vanessa (My University, 2024)
The entomopathogenic fungus Beauveria bassiana is one of the main microorganisms used in the composition of biological products. Although commercial production of this bioagent is traditionally based on solid state cultivation, submerged cultivation has received increasing attention in the industry due to its numerous advantages compared to the solid cultivation process. In this context, the objective of this work was, in partnership with the company Dillon Biotechnology, to optimize the production of submerged spores (SS) of B. bassiana and scale up the submerged cultivation of the fungus in a pilot-scale bioreactor, with a focus on studying the IBCB 868, IBCB 66 and CBMAI 1306 strains. The submerged spores produced were formulated and subjected to stability and efficacy evaluations in controlling the two-spotted mite (Tetranychus urticae). The optimization of the culture medium, carried out using the Plackett-Burman (PB) experimental design followed by the central composite rotational design (CCRD), led to the achievement of SS concentrations exceeding 1×109 SS mL-1 in just three days of growth for the IBCB 868 strain of B. bassiana. Additionally, cultivations in a laboratory-scale bioreactor, conducted with the same strain, made it possible to identify the ideal pH and dissolved oxygen conditions for optimal growth of the fungus. Solid formulations were developed for the strains based on growth in the optimized culture medium. The formulated products proved effective in controlling the spider mite and remained stable after 90 days of storage under refrigeration (4 ± 1 ºC) with a UFC g-1 concentration exceeding 1×109. Finally, the scaling up of the cultivation conducted with the IBCB 868 strain in a 500-liter pilot-scale bioreactor, with a 350-liter operational volume, demonstrated the possibility of obtaining substantial quantities of B. bassiana SS, above 1×109 SS mL-1 , in a short period of just three days. The results obtained in this study represent an important contribution to expanding knowledge about liquid culture, a promising technology for the development of products based on entomopathogenic fungi. [resumo fornecido pelo autor]
O fungo entomopatogênico Beauveria bassiana consiste em um dos principais microrganismos utilizados na composição de produtos biológicos. Embora a produção comercial deste bioagente seja tradicionalmente baseada no cultivo em estado sólido, o cultivo submerso tem recebido crescente atenção na indústria devido às suas numerosas vantagens em comparação ao processo de cultivo sólido. Nesse contexto, o objetivo deste trabalho foi, em parceria com a empresa Dillon Biotecnologia, otimizar a produção de esporos submersos (ES) de B. bassiana e escalonar o cultivo submerso do fungo em biorreator de escala piloto, sendo estudadas as linhagens IBCB 868, IBCB 66 e CBMAI 1306. Os esporos submersos produzidos foram formulados e submetidos a avaliações de estabilidade e eficácia no controle do ácaro rajado (Tetranychus urticae). A otimização do meio de cultura, realizada a partir do planejamento experimental Plackett-Burman (PB) seguido do delineamento composto central rotacional (DCCR), resultou na obtenção de concentrações de ES acima de 1×109 ES mL-1 em apenas três dias de crescimento para a linhagem IBCB 868 de B. bassiana. Adicionalmente, os cultivos em biorreator de escala laboratorial, conduzidos com a mesma linhagem, possibilitaram a identificação das condições ideais de pH e oxigênio dissolvido (OD) para o crescimento ótimo do fungo. Formulações sólidas foram desenvolvidas para as linhagens, a partir do crescimento no meio de cultura otimizado. Os formulados demonstraram ser eficazes no controle do ácaro rajado e mantiveram-se estáveis após 90 dias de armazenamento sob refrigeração (4 ± 1 ºC) com concentração de UFC g-1 superior a 1×109. Por fim, o escalonamento do cultivo realizado com a linhagem IBCB 868 em biorreator de escala piloto de 500 litros, com 350 litros de volume operacional, mostrou a possibilidade de obter quantidades substanciais de ES do fungo B. bassiana, acima de 1×109 ES mL-1, em um curto período de apenas três dias. Os resultados obtidos neste estudo representam uma importante contribuição para a ampliação do conhecimento acerca da cultura líquida, uma tecnologia promissora para o desenvolvimento de produtos à base de fungos entomopatogênicos. [resumo fornecido pelo autor]
Keywords: Fungos como agentes no controle biológico de pragas; Fungos -Controle biológico; Microorganismos; Biotecnologia; Fungi as biological pest control agents; Fungi - Biological control; Microorganisms; Biotechnology